NEUROSARCOIDOSIS: A CASE REVIEW. (February 2015) - Adams, Stuart; Varallo-Nunez, Ana
Abstract : Neurosarcoidosis refers to sarcoidosis involving the central nervous system. Approximately 5–10% of people with systemic sarcoidosis develop central nervous system involvement and half of these present with neurological disease at the time of their initial sarcoidosis diagnosis. We report a case of neurosarcoid in a 55-year-old lady of angloceltic origin who presented with 3 months history of memory disturbances and 2 days of confusion with no history of trauma, fever or vomiting. On examination she was confused but otherwise was normal. The CT of brain showed hydrocephalus with increased intracranial pressure consistent with outflow obstruction. She was treated with bilateral EVD drainage with partial improvement of symptoms. A follow up MRI show ependymal and dural enhancement. Repeated CSF studies showed high protein levels and normal glucose, the cultures were negative. Stereotactic biopsies of choroid plexus and septum pellucidum showed multiple non-necrotising granulomas. Special stains were negative for organisms. PCR for mycobacteria tuberculosis and avium complex was negative. Subsequent CT chest showed several small benign-appearing right upper lobe lung nodules. A preferred diagnosis of sarcoidosis was made with brain and meningeal and possible lung involvement.